Analysis of the Effect of Company Micro Fundamental Factors on Company Value in Companies Listed in LQ 45 Index - Hilal, Achmad; Samono, Samono (International Journal of Economics and Financial Issues, 2019)
This study shows the effect of the company micro fundamental factors on the company value registered in the LQ 45 Index (2012-2016). Company value is paid by prospective investors when a company is sold. The company is projected using the Tobin's Q ratio. The company micro fundamental factors in this study are Current Ratio, Debt to Equity Ratio, Return on Assets, and Earning per Share. Current Ratio is used to measure the ability of a company to fulfill its short-term obligate ions. Debt to Equity Ratio is used to assess the debt with equity that reflects the ability of a company to fulfill its obligations. Return on Assets is used to measure the ability of company to generate profits with assets used. Earnings per share is used to measure the achievement of the management in Achieving profits for shareholders. The design of this study is panel data regression using EViews 9 program. The analysis of the data in this study is the F Test for simultaneous and correlation tests (Adjusted R-Square). In this study, Debt to Equity Ratio and Return on Assets have positive and significant effect on the company's value (Tobin's Q) .Earning per Share has a negative and significant effect on company value (Tobin's Q). Current ratio has no significant negative effect on company value (Tobin's Q). Simultaneously, Current Ratio, Debt to Equity Ratio, Return on Assets, and Earning per Share has significant impact on company value (Tobin's Q) with adjusted R-Square 0.972082. T means Tobin's Q 97.2082% can be explained from the combination of the four independent variables. Keywords: Company Value, Current Ratio, Debt to Equity Ratio, Return on Assets, Earning per Share JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.8346